Quantitative proteomics of Arabidopsis shoot microsomal proteins reveals a cross‐talk between excess zinc and iron deficiency. Issue 7 (2nd March 2015) - Zargar, Sajad Majeed; Kurata, Rie; Inaba, Shoko; Oikawa, Akira; Fukui, Risa; Ogata, Yoshiyuki; Agrawal, Ganesh Kumar; Rakwal, Randeep; Fukao, Yoichiro
<x xml:space="preserve">Abstract</x> Iron (Fe) deficiency significantly effects plant growth and development. Plant symptoms under excess zinc (Zn) resemble symptoms of Fe‐deficient plants. To understand cross‐talk between excess Zn and Fe deficiency, we investigated physiological parameters of Arabidopsis plants and applied iTRAQ‐OFFGEL quantitative proteomic approach to examine protein expression changes in microsomal fraction from Arabidopsis shoots under those physiological conditions. Arabidopsis plants manifested shoot inhibition and chlorosis symptoms when grown on Fe‐deficient media compared to basal MGRL solid medium. iTRAQ‐OFFGEL approach identified 909 differentially expressed proteins common to all three biological replicates; the majority were transporters or proteins involved in photosynthesis, and ribosomal proteins. Interestingly, protein expression changes between excess Zn and Fe deficiency showed similar pattern. Further, the changes due to excess Zn were dramatically restored by the addition of Fe. To obtain biological insight into Zn and Fe cross‐talk, we focused on transporters, where STP4 and STP13 sugar transporters were predominantly expressed and responsive to Fe‐deficient conditions. Plants grown on Fe‐deficient conditions showed significantly increased level of sugars. These results suggest that Fe deficiency might lead to the disruption of sugar synthesis and utilization.